Association between metabolic syndrome and Behçet's disease: A nationwide population‐based study. Issue 7 (7th May 2021) - Lee, JiHyun; Yoo, SeungAh; Han, Kyung Do; Han, Ju Hee; Bang, Chul Hwan; Park, YoungMin; Lee, Jun Young; Park, Yong‐Gyu; Lee, YoungBok
Abstract: Metabolic syndrome (MetS) is characterized by insulin resistance, high blood pressure/sugar, dyslipidemia, and obesity. Whether MetS and its components affect the development of Behçet's disease (BD) remains unclear. This study was performed to investigate the associations between metabolic syndrome and risk of BD using nationwide population data. We conducted a retrospective cohort study of 10 505 818 Korean subjects who received health checkups in 2009–2012. Patients were classified into a MetS and its components group and were followed‐up until 2016 for new‐onset BD. A Cox proportional hazards model was used to assess the independent or synergistic effects of MetS and its components on the risk of incident BD. Compared to subjects without MetS components, the hazard ratio (HR) for development of BD in patients with MetS was 0.874 (95% confidence interval [CI]: 0.819–0.933) and this association was more prominent when all components of MetS were present (HR = 0.675, 95% CI = 0.571–0.798). Subjects with low high density lipoprotein (HDL) has a significantly increased risk of the development of BD (HR = 1.51, 95% CI = 1.4–1.594) compared to controls. This study showed that the incidence of Behçet's disease was reduced in subjects with MetS. Moreover, the presence of MetS components, with the exception of HDL, was negatively related to the development of BD.